RELATIONSHIP OF EDUCATION AND HEALTH - Ergasheva, Sabina; Ibragimova , Laylo (Innovative Development in Educational Activities, 2023)
The relationship between education and health is complex and multifaceted. Higher levels of education are consistently associated with better health outcomes, including lower rates of chronic diseases, longer life expectancy, and overall improved well-being. This relationship can be attributed to the knowledge and skills acquired through education, which enable individuals to make informed decisions about their health and access healthcare services. Additionally, higher education is often linked to higher income levels, which in turn can lead to better access to healthcare and healthier lifestyle choices. However, it is important to acknowledge the bidirectional nature of this relationship, as poor health can also impact educational attainment. Policymakers and educators must recognize and address the interconnectedness of education and health in order to promote overall well-being and improve the lives of individuals and communities.